2000
DOI: 10.1037/0735-7028.31.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the personal lives of psychotherapists and research psychologists.

Abstract: Being a psychotherapist is a complex challenge. Research has suggested that therapists are changed by their work, but it has not been clear whether these changes are the same for research psychologists and practitioners. Representatives of these 2 groups were surveyed. Although therapists reported more anxiety, depression, and emotional exhaustion than did researchers, they were also more satisfied with their lives and more likely than researchers to feel that their work had influenced them in positive ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 22 publications
2
43
0
1
Order By: Relevance
“…Clinicians may be vulnerable to symptoms of depression (Gilroy, Carroll, & Murra, 2002;Heath, 1991;Pope & Tabachnick, 1994) and when compared with research psychologists, they have reported higher rates of anxiety, depression, and emotional exhaustion (Radeke & Mahoney, 2000). Moderate to high levels of stress were observed in a sample of British clinical psychologists, and specifically, women and the less experienced, less socially supported participants reported greater psychological distress (Cushway & Tyler, 1996).…”
Section: Self-carementioning
confidence: 99%
“…Clinicians may be vulnerable to symptoms of depression (Gilroy, Carroll, & Murra, 2002;Heath, 1991;Pope & Tabachnick, 1994) and when compared with research psychologists, they have reported higher rates of anxiety, depression, and emotional exhaustion (Radeke & Mahoney, 2000). Moderate to high levels of stress were observed in a sample of British clinical psychologists, and specifically, women and the less experienced, less socially supported participants reported greater psychological distress (Cushway & Tyler, 1996).…”
Section: Self-carementioning
confidence: 99%
“…It is possible that she is correct about the depressive character structure. Radeke and Mahoney (2000), for example, found that psychologists who were psychotherapists were more likely than those who were researchers to report depression and anxiety. But the support for McWilliams' observation concerning childhood relational difficulties seems quite strong.…”
Section: A Career Development Perspectivementioning
confidence: 96%
“…Goodyear, Lichtenberg, and McPherson (2001) found in their national survey of counseling psychologists that practitioners reported less happy childhoods than those who were university faculty. Radeke and Mahoney (2000) found that psychologists who were psychotherapists were more likely than those who were researchers to have experienced childhood abuse. Elliott (1993) found that women psychotherapists, compared with women in other professions reported having experienced higher rates of physical abuse, sexual molestation, parental alcoholism, psychiatric hospitalization of a parent, death of a family member, and greater family dysfunction in their families of origin.…”
Section: A Career Development Perspectivementioning
confidence: 97%
“…Professionals who care for others are vulnerable to occupational stress as the result of their care-giving role. For example, practicing psychotherapists consistently report significant levels of emotional exhaustion, anxiety, and depression (Norcross, 2000;Radeke & Mahoney, 2000). One recent study of psychologists demonstrated that 4 in 10 were experiencing clinically significant levels of distress (May & O'Donovan, 2007).…”
Section: Mindfulness and The Integration Of Self-care In Clinical Tramentioning
confidence: 96%